India's role in South Asia - Mendis, Vernon L. B.; Bandaranaike Centre for International Studies (Colombo : Bandaranaike Centre for International Studies, S.W.R.D. Bandaranaike National Memorial Foundation, 1992)
Includes papers presented at the Seminar on India's Role in South Asia, held under the auspices of the Bandaranaike Centre for International Studies in June 1991.
Includes bibliographical references and index.
Keywords: South Asia -- Foreign relations -- India -- Congresses; India -- Foreign relations -- South Asia -- Congresses; India -- Foreign relations -- 1947-1984 -- Congresses; India -- Foreign relations -- 1984- -- Congresses